FOREIGN DIRECT INVESTMENT AND EMPLOYMENT AS PRIMARY LONG-RUN DRIVERS OF ECONOMIC GROWTH - Pratysto, Tangguh; Herawati, Mesi; Sunarya, Iqbal Banyu (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Although the macroeconomic determinants of growth are studied at length, there is still a lack of study on many aspects of the BRICS, which now includes the new members Egypt, Ethiopia, Iran, Saudi Arabia, the UAE, and Indonesia, especially about the simultaneous consideration of unemployment along with FDI, trade openness, and inflation in a single panel model. The objective of this paper is to investigate the short- and long-run influence on GDP growth by accounting for heterogeneity within this community. Quantitative panel data analysis employing Panel ARDL with PMG estimator on secondary annual data (1991–2023) of 11 BRICS countries obtained from World Bank World Development Indicators. While FDI is positive and significant in the long run, unemployment is negative and significant (-0.217, p=0.008). Trade openness and Inflation are positive but not statistically significant. In the short run, unemployment is negative (-1.528, p=0.002); the error-correction term is -0.681 (p < 0.001), implying that 68% of the adjustment occurs annually. FDI and unemployment are identified as major long-run determinants, with rapid equilibrium adjustment. The innovation lies in the extended BRICS panel and the more recent disclosure of more potent effects of unemployment on structural turns. To this end, policies should be oriented toward promoting FDI and reducing unemployment to ensure sustained and inclusive growth, and institutional improvements would further enhance the gains from trade.